Proceedings of the 3rd Augmented Human International Conference 2012
DOI: 10.1145/2160125.2160132
|View full text |Cite
|
Sign up to set email alerts
|

Relation between location of information displayed by augmented reality and user's memorization

Abstract: This study aims to investigate the effectiveness of Augmented Reality (AR) on user's memory skills when it is used as an information display method. By definition, AR is a technology which displays virtual images on the real world. These computer generated images naturally contain location information on the real world. It is also known that humans can easily memorize and remember information if this information is retained along with some locations on the real world. Thus, we hypothesize that displaying annot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 9 publications
2
18
0
Order By: Relevance
“…7. And the assembly sequence is set as (4)-(1,3,5,6)- (8,17,18,9)- (11,16,15,14,13)-(top cover)-(bolts)-(12)-(bolts)-(7,10)-(bolts)-(2,19)-(bolts).…”
Section: Results and Analysis Of The Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…7. And the assembly sequence is set as (4)-(1,3,5,6)- (8,17,18,9)- (11,16,15,14,13)-(top cover)-(bolts)-(12)-(bolts)-(7,10)-(bolts)-(2,19)-(bolts).…”
Section: Results and Analysis Of The Experimentsmentioning
confidence: 99%
“…Virtual annotations, such as labels, images, and some other ways, were often used to annotate physical objects. Displaying annotations by aid of AR may have better effects on the user's memory skill, if they are associated with the location of the target object on the real world [14]. Therefore, the layout of virtual annotations was one of the key techniques in this kind of AR applications.…”
Section: Related Researchmentioning
confidence: 99%
“…Results showed that displaying visual instructions at the locations to be memorized is useful for memorizing them visually, as in the case of the user study in which individual semantic memory was used as the memorization target [5].…”
Section: Discussionmentioning
confidence: 98%
“…As a first step, we conducted a user study in [5], and we verified that displaying annotations using AR can enhance a user's memory * e-mail: {yuichiro-f, goshiro, takafumi-t, miyazaki, kato} @is.naist.jp skill in a task in which users are instructed to memorize individual symbols, if the annotations are displayed near the real-world location of the target object instead of an unrelated location. In this paper, we conducted another user study in which users were instructed to memorize continuous task processes of more realistic tasks, by picking blocks from some drawers in order to evaluate the relation between the features of AR and user memorization.…”
Section: Introduction and Related Workmentioning
confidence: 99%
“…They hypothesize that this difference may be due to the kinetic component of moving the projector. Fujimoto et al [8] studied the effect of adding visual cues on targets to be memorized using an HMD system. They found that associating visual anotations with real world locations enhances the learning.…”
Section: Projection Systemsmentioning
confidence: 99%